Use of indocyanine green fluorescence during hepatobiliary surgery - Maharjan, Dhiresh Kumar; Thapa, Prabin Bikram (Journal of Kathmandu Medical College, 2020)
Background: Indocyanine green fluorescence image has been used in hepatobiliary surgery, which was mainly started by Japanese surgeons to visualize hepatobiliary structures probably because it is regarded as a reagent for estimation of hepatic function. Objectives: The objective of this study is to see the feasibility of use of indocyanine green in our setting during hepatobiliary surgery and its potential applications in the surgical treatment of benign and malignant liver pathology along with its selective use during difficult cholecystectomy to visualize extrahepatic biliary radical. Methodology: This is a prospective cross sectional observational study performed including all consecutive patients who were posted for liver resection, both benign or malignant and selectively used in biliary surgery when biliary anatomy was uncertain. Results: A total of thirty-nine patients had usage of indocyanine green, with a mean age of 51.6 ± 11.6 years (range, 31-75 years). In all our patients we were able to visualize the biliary system and liver parenchymal lesion.In the selective use of indocyanine green during difficult biliary anatomy during laparoscopic cholecystectomy 15/400 (3.75%), we were able to delineate biliary tree and hence five patients (1.2%) had to be converted to open cholecystectomy further preventing injury to the bile duct. Conclusion: Indocyanine green fluorescence imaging can be used safely and easily to identify liver tumors, hepatic segments, and extrahepatic bile ducts in real time during open and minimally invasive surgery. This allows surgeons to map the anatomical variations, status of resection margin and prevent surgical complications.